2021
DOI: 10.34312/jmathedu.v2i2.11105
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kesulitan Pembelajaran Daring pada Mata Pelajaran Matematika di Tengah Pandemi Covid-19

Abstract: This study aims to describe the difficulties of online learning in mathematics subjects in the midst of the Covid-19 pandemic. This research is a descriptive research with a quantitative approach. The subjects in this study were students of class VIII 3 and VIII 4 at SMP Negeri 4 Gorontalo. Data collection was obtained from data from questionnaires and student interviews. To see student responses in online learning on mathematics subjects in the midst of the Covid-19 pandemic, a questionnaire was given with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…Ini relevan dengan penelitian Jannah & Pujiastuti (2021) bahwa lingkungan keluarga begitu berpengaruh dengan hasil belajar siswa pada saat pembelajaran daring. Belum lagi ditambah dengan sulitnya sarana dan prasarana siswa yang membuat guru bingung harus melakukan apa di era pandemic Covid-19 itu, hal ini dibuktikan dengan penelitian yang mengatakan proses pembelajaran matematika di masa pandemic Covid-19 siswa mengalami kesulitan dengan kategori sedang hingga tinggi (Riskawati et al, 2021) sehingga tidak diragukan jika sekarang ini banyak siswa yang tidak memahami materi-materi yang diajarkan selama 2 tahun ke belakang, tentunya ini mengakibatkan kesulitan yang tinggi untuk siswa memahami materi dikelas IX yang mana sebagian besar materinya membutuhkan pemahaman dari materi sebelumnya, ini relevan dengan pernyataan Hutagalung (2018) dalam penelitiannya yang mengemukakan Pengetahuan konsep yang kuat akan mendorong pengetahuan prosedural matematika siswa.…”
Section: Pembahasanunclassified
“…Ini relevan dengan penelitian Jannah & Pujiastuti (2021) bahwa lingkungan keluarga begitu berpengaruh dengan hasil belajar siswa pada saat pembelajaran daring. Belum lagi ditambah dengan sulitnya sarana dan prasarana siswa yang membuat guru bingung harus melakukan apa di era pandemic Covid-19 itu, hal ini dibuktikan dengan penelitian yang mengatakan proses pembelajaran matematika di masa pandemic Covid-19 siswa mengalami kesulitan dengan kategori sedang hingga tinggi (Riskawati et al, 2021) sehingga tidak diragukan jika sekarang ini banyak siswa yang tidak memahami materi-materi yang diajarkan selama 2 tahun ke belakang, tentunya ini mengakibatkan kesulitan yang tinggi untuk siswa memahami materi dikelas IX yang mana sebagian besar materinya membutuhkan pemahaman dari materi sebelumnya, ini relevan dengan pernyataan Hutagalung (2018) dalam penelitiannya yang mengemukakan Pengetahuan konsep yang kuat akan mendorong pengetahuan prosedural matematika siswa.…”
Section: Pembahasanunclassified
“…Implementation of online learning at a public high school in Jambi Province was carried out using several supporting applications such as WhatsApp Grub and Google meet. Riskawati et al (2021) revealed that the implementation of online learning itself prioritiez student's critical thinking skills and their accuracy in receiving and processing information presented online. The use of online learning systems sometimes causes various difficulties in the learning process faced by students.…”
Section: A Introductionmentioning
confidence: 99%
“…The use of online learning systems sometimes causes various difficulties in the learning process faced by students. Based on research by Riskawati et al (2021), it is known that the difficulties that the students often experience in online learning are limited internet quota, unstable internet network due to the location where students live in rural areas, some students do not have smartphones and have difficulty understanding the material.…”
Section: A Introductionmentioning
confidence: 99%
See 1 more Smart Citation